Micrometeorological alterations in soybeans grown under different water regimes - Berlato, Moacir A.; Bergamaschi, Homero (Pesquisa Agropecuaria Brasileira, 1992)
In Taquari, RS, Brazil (Lat. 29o48’S, Long. 51o48’W, and Alt. 76 m), micrometeorological alterations were evaluated on two Bragg soybean (Glycine max (L.) Merrill) communities submitted to different water regimes: irrigated (plot size of 2.500 m2) and non-irrigated (2.100 m2). Sowing date was November 21, 1985, and row space of 0,68 m to accomplish a population density of 4 x 105 plants/ha. During diurnal period the air temperature and the air vapor saturation deficit were dependent on the surface energy balance, which was influenced mostly by the soil water potential. Under conditions of water restrictions these parameters presented higher values than those obtained under no water restrictions, determining in this way higher atmosphere evaporative demand near to the plants.